Costly reproductive competition between females in a monogamous cooperatively breeding bird - Nelson-Flower, Martha J. (The Royal Society, 2013)
In many cooperatively breeding societies, only a few socially dominant individuals in a group breed, reproductive skew is high, and reproductive conflict is common. Surprisingly, the effects of this conflict on dominant reproductive success in vertebrate societies have rarely been investigated, especially in high-skew societies. We examine how subordinate female competition for breeding opportunities affects the reproductive success of dominant females in a monogamous cooperatively breeding bird, the Southern pied babbler (Turdoides bicolor). In this species, successful subordinate reproduction is very rare, despite the fact that groups commonly contain sexually mature female subordinates that could mate with unrelated group males. However, we show that subordinate females compete with dominant females to breed, and do so far more often than expected, based on the infrequency of their success. Attempts by subordinates to obtain a share of breeding impose significant costs on dominant females: chicks fledge from fewer nests, more nests are abandoned before incubation begins, and more eggs are lost. Dominant females appear to attempt to reduce these costs by aggressively suppressing potentially competitive subordinate females. This empirical evidence provides rare insight into the nature of the conflicts between females and the resultant costs to reproductive success in cooperatively breeding societies.